Exploring the Dynamic Interplay between Note-taking Strategies and Reading Comprehension Performance of Moroccan EFL Students: A Quasi-Experimental Study - Bani Koumachi (Randwick International of Education and Linguistics Science Journal, 2020)
Recently, at Moroccan tertiary level and in the area of student practices, little attention has been brought particularly to the skill of note-taking and active reading comprehension, and an insightful and in-depth understanding of how students learn from lectures could presumably be valuable in understanding and unravelling the intricacies of possible positive results of their note-taking behavior. The current study focuses mainly on the instruction of students into the systems of note-taking and how that affects their level of reading comprehension. Therefore, the effort reported here attempts to assess the students’ current systems of notetaking and how they contribute to reach a full understanding of reading comprehension texts. The participants were 94 Semester-One students at the department of the English Studies at Ibn Tofail University, School of Arts and Humanities in Kénitra, Morocco. The data of the present study were collected by means of a TOEFL iBT Reading Practice comprehension test (i.e., post-test), and strategy training equating note-taking schemas and reading comprehension texts. The findings have showcased that after having been instructed through many sessions of note-taking, students felt that their process of reading comprehension is enhanced as they were able to organize their ideas and information from the text, stay focused and engaged while reading, and keep a record of reading material to use it later. This is solid proof that they critically used and retained what they read.